Teacher’s Views on the Relevance of Technical and Vocational Education and Training (TVET) College Curricula to Labour Market - Nkwanyane, Themba; Makgato, Moses; Ramaligela, Sylvia (Online Journal for TVET Practitioners, 2020)
The main objectives of Technical and Vocational Education and Training (TVET) colleges is to impart skills and develop the youth and young adults with relevant skills for transition into the labour market. The realisation of these objectives can be met if TVET colleges offer relevant and responsive curricula in line with current labour market trends. The aim of this study is to present the findings of lecturer’s perceptions on the responsiveness of National Certificate Vocational (NC V) civil engineering curriculum to labour market. A qualitative case study was employed in this study. This research study was conducted through a semi-structured interviews with twelve lecturers from four TVET colleges in South Africa. Study findings revealed that: 1. Lecturers perceive that NC V civil engineering curriculum does not provide adequate skills for the labour market 2. The NC V civil engineering curriculum need to be revised and updated as a matter of urgency. Therefore there is an urgent need to review and update the NC V civil engineering curriculum in line with labour market development. The researcher recommend that NC V civil engineering curriculum reviewal process need to involve the Department of Higher Education and Training (DHET), subject specialist, industry experts and all other stakeholders. Failure to address this issue will result in South Africa’s TVET colleges offering irrelevant and outdated curricula content which lags behind in the modern era of technological advancement.